STARCH HYDROLYSIS BY STREPTOCOCCUS EQUINUS - Dunican, Lawrence K. (1962)
Dunican, Lawrence K. (Cornell University, Ithaca, N. Y.) and Harry W. Seeley. Starch hydrolysis by Streptococcus equinus. J. Bacteriol. 82:264–269. 1962.—In a study of starch hydrolysis by strains of Streptococcus equinus, 52 isolates were obtained and their amylolytic abilities determined. It was found that all the strains could hydrolyze starch to some extent when grown in the presence of an easily fermentable carbohydrate, viz., glucose. Without this carbohydrate the organisms did not hydrolyze starch. The hydrolysis of starch was inhibited when the organisms were grown in an atmosphere of 5% CO(2) and 95% N(2), even if grown in the presence of a fermentable monosaccharide. S. bovis, which was used as a reference organism, readily hydrolyzed starch in the absence of monosaccharides and in atmospheres containing CO(2). In no instance did S. equinus hydrolyze the starch to the level of reducing sugars. Negligible amounts of reducing sugars were recovered when the cell-free filtrates of S. equinus were incubated with starch. With S. bovis, the yield of reducing sugars under such conditions was almost quantitative. These facts extend further the differences between these related organisms. The ability to synthesize an internal starchlike polysaccharide was noted in most of the strains of S. equinus. Synthesis was found when the organisms were grown on maltose or on a starch medium containing a small amount of fermentable monosaccharide.